Life Sciences and Health in South West Wales: A Sub-regional Innovation Ecosystem - Gareth Davies (Entrepreneurial Learning City Regions, 2018)
This chapter describes how efforts to develop the Life Sciences sector in south Wales have been undertaken through structured efforts of Understanding, Acting and Measuring, resulting in new ventures formed through spin-outs to commercialise research output and collaboration with other enterprises. Building upon concepts of clustering and regional innovation systems, the approach demonstrates the harnessing of a long-term strategy involving smart specialisation resulting in emerging and meaningful economic impact. Networking and knowledge exchange are shown as core components of a system reaching across wider sectors involving a diversity of skills.